Applied Cryptography and Network Security 20th International Conference, ACNS 2022, Rome, Italy, June 20-23, 2022, Proceedings - Ateniese, Giuseppe; Venturi, Daniele (Cham : Springer International Publishing : Imprint: Springer, 2022)
The LNCS volume 13269 constitutes the proceedings of the 20th International Conference on Applied Cryptography and Network Security, ACNS 2022, which will take place in a hybrid mode in Rome, Italy in June 2022. The 44 full papers together with 5 short papers presented in this proceeding were carefully reviewed and selected from a total of 185 submissions. They were organized in topical sections as follows: Encryption, Attacks, Cryptographic Protocols, System Security., Cryptographic Primitives, MPC, Blockchain, Block-Cyphers, and Post-Quantum Cryptography.
Encryption -- Attacks -- Cryptographic Protocols -- System Security -- Cryptographic Primitives -- MPC -- Blockchain -- Block-Cyphers -- Post-Quantum Cryptography.
Keywords: Data protection; Data structures (Computer science).; Information theory; Operating systems (Computers).; Application software; Cryptography; Data encryption (Computer science).; Data and Information Security; Data Structures and Information Theory; Operating Systems; Computer and Information Systems Applications; Cryptology; Security Services